Outcomes of Autologous Free Flap Reconstruction Following Infected Device Explantation - Mitchell, David; Asaad, Malke; Slovacek, Cedar; Selber, Jesse C.; Clemens, Mark W.; Chu, Carrie K.; Mericli, Alexander F.; Largo, Rene D.; Butler, Charles E. (Journal of Reconstructive Microsurgery, 2022)
Background Following implant-based breast reconstruction (IBR) infection and explantation, autologous reconstruction is a common option for patients who desire further reconstruction. However, few data exist about the outcomes of secondary autologous reconstruction (i.e., free flap breast reconstruction) in this population. We hypothesized that autologous reconstruction following infected device explantation is safe and has comparable surgical outcomes to delayed-immediate reconstruction.Methods We conducted a retrospective analysis of patients who underwent IBR explantation due to infection from 2006 through 2019, followed by secondary autologous reconstruction. The control cohort comprised patients who underwent planned primary delayed-immediate reconstruction (tissue expander followed by autologous flap) in 2018.Results We identified 38 secondary autologous reconstructions after failed primary IBR and 52 primary delayed-immediate reconstructions. Between secondary autologous and delayed-immediate reconstructions, there were no significant differences in overall complications (29 and 37%, respectively, p = 0.45), any breast-related complications (18 and 21%, respectively, p = 0.75), or any major breast-related complications (13 and10%, respectively, p = 0.74). Two flap losses were identified in the secondary autologous reconstruction group while no flap losses were reported in the delayed-immediate reconstruction group (p = 0.18).Conclusion Autologous reconstruction is a reasonable and safe option for patients who require explantation of an infected prosthetic device. Failure of primary IBR did not confer significantly higher risk of complications after secondary autologous flap reconstruction compared with primary delayed-immediate reconstruction. This information can help plastic surgeons with shared decision-making and counseling for patients who desire reconstruction after infected device removal.
Keywords: secondary autologous reconstruction; infection; implant